2003
DOI: 10.1007/bf03166686
|View full text |Cite
|
Sign up to set email alerts
|

Reaction kinetics analysis to estimate in vivo decay rate of EPR signals of a nitroxide radical in the brain and the inferior vena cava of rats

Abstract: To clarify the degree of the influence of the peripheral organs on the temporal changes in the electron paramagnetic resonance (EPR) signal intensity of a nitroxide radical permeating the bloodbrain barrier, 3-hydroxymethyl-2,2,5,5-tetramethylprrotidine-l-oxyl (hydroxymethyl-PROXYL), in the brain, temporal changes in the EPR signal in the brain or inferior vena cava of rats were measured by an in vivo 700 MHz radio-frequency EPR spectrometer equipped with a bridged loop-gap resonator ora surface-coil-type reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…A previous phantom study confirmed that the FWHM‐to‐gradient ratio could serve as an index of the spatial resolution (9). In our previous study the FWHM‐to‐gradient ratio of the EPR images of the nitroxide‐treated rats was about 2 mm (5, 6, 9).…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…A previous phantom study confirmed that the FWHM‐to‐gradient ratio could serve as an index of the spatial resolution (9). In our previous study the FWHM‐to‐gradient ratio of the EPR images of the nitroxide‐treated rats was about 2 mm (5, 6, 9).…”
Section: Methodsmentioning
confidence: 89%
“…A 700 MHz EPRI system was constructed at our institute (as previously described in detail (5, 6, 8–10)) and consisted of a main electromagnet, a pair of magnetic field scan coils, a pair of magnetic field gradient coils, a pair of magnetic field modulation coils, a two‐gap loop‐gap EPR resonator (11) (inner diameter = 41 mm; axial length = 10 mm; unloaded Q = 480), RF circuits for homodyne detection (ca. 700 MHz), and intermediate frequency circuits for lock‐in detection at a modulation frequency of 100 kHz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When peak-to-peak line width of the ESR signal of TEMPOL exhibits no temporal changes in a target organ, the peak-to-peak height can then be used as the signal intensity. [16][17][18][19][20] In the target organs, changes in the signal intensity correspond to changes in the TEMPOL concentration. When there is good linearity in a semi-logarithmic plot of the signal intensity with high reproducibility after a TEMPOL injection, this is indicative of the pseudo-first-order kinetics of the TEMPOL decrease in the target organ.…”
Section: In Vivo Esr Measurementsmentioning
confidence: 99%
“…Yokoyama et al proposed that estimations of the reducing ability of nitroxyl radicals could be calculated by using an equation that expresses the nitroxyl radical concentration in the target organ. 19,20 The target organ (Xn) as a function of time (t) approximates Xn = Xn 0 exp (-k0nt), where Xn 0 is the initial value of the concentration and k0n is the first-order rate constant (equal to log 2/half-life). The half-lives of TEMPOL in the target organs were used as the parameter to estimate the decay rate of TEMPOL, as this parameter was not influenced by reduction in the other organs.…”
Section: In Vivo Esr Measurementsmentioning
confidence: 99%